Homeopathy for Gallstones: A Holistic Approach to Managing Symptoms (Homoeopathy for All, 2024)
Solid particles called gallstones  develop in the gallbladder, a little  organ under the liver. The size and  quantity of these stones might vary,  resulting in a variety of problems  and symptoms. It is essential to  comprehend gallstone production,  symptoms, diagnosis, and treatment  in order to effectively manage this  prevalent ailment.
Keywords: Cholelithiasis; Biliary calculi; Gallbladder stones; Cholesterol stones; Pigment stones; Cholecystitis